Mass mediatisation of social media - Marion Olga Alina; Donal McCracken (Communicare)
Based on the 2016 presidential election in Uganda as covered on the NTV Facebook page, this paper, emanating from a doctoral study, shows how the medium of television has mass mediatised Facebook. The onset of social media has meant that audiences increasingly turn to such platforms for their information needs, including news. As a consequence, the traditional media’s role of providing such news and information updates is demoted and threatened. In order to stay relevant, mass media has had to join social media platforms to provide the aforementioned information/news. In attempting to do so, mass media has consequently mediatised social media, especially as seen through the lens of the agenda-setting theory, which this paper argues is in contrast with the discursive nature of social media as a public sphere.